Biofabrication of human articular cartilage: a path towards the development of a clinical treatment. (21st August 2018) - Onofrillo, Carmine; Duchi, Serena; O'Connell, Cathal D; Blanchard, Romane; O'Connor, Andrea J; Scott, Mark; Wallace, Gordon G; Choong, Peter F M; Di Bella, Claudia
Abstract: Cartilage injuries cause pain and loss of function, and if severe may result in osteoarthritis (OA). 3D bioprinting is now a tangible option for the delivery of bioscaffolds capable of regenerating the deficient cartilage tissue. Our team has developed a handheld device, the Biopen, to allow in situ additive manufacturing during surgery. Given its ability to extrude in a core/shell manner, the Biopen can preserve cell viability during the biofabrication process, and it is currently the only biofabrication tool tested as a surgical instrument in a sheep model using homologous stem cells. As a necessary step toward the development of a clinically relevant protocol, we aimed to demonstrate that our handheld extrusion device can successfully be used for the biofabrication of human cartilage. Therefore, this study is a required step for the development of a surgical treatment in human patients. In this work we specifically used human adipose derived mesenchymal stem cells (hADSCs), harvested from the infra-patellar fat pad of donor patients affected by OA, to also prove that they can be utilized as the source of cells for the future clinical application. With the Biopen, we generated bioscaffolds made of hADSCs laden in gelatin methacrylate, hyaluronic acid methacrylate and cultured in the presence of chondrogenic stimuli for eight weeks in vitro . A comprehensive characterisation including gene and protein expression analyses, immunohistology, confocal microscopy, second harmonic generation, light sheet imaging, atomic force mycroscopy and mechanical unconfined compression demonstrated that our strategy resulted in human hyaline-like cartilage formation. Our in situ biofabrication approach represents an innovation with important implications for customizing cartilage repair in patients with cartilage injuries and OA.